Influence of Cultural and Linguistic Peculiarities of Mastering the Russian Language by Chinese Students - Клочко, Т. В.; Малишева, О. Н. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The given article is devoted to the research of the problem of optimization of the training process in teaching Chinese students Russian language. Authors review social, cultural and cultural-linguistic peculiarities that have a direct impact on the students’ perception of a foreign language. The article describes some methods of training Chinese students in order to find the ways of optimization of this process. Some peculiarities of Chinese and Russian pedagogical systems and teaching process organization in Chinese and Ukrainian higher educational establishments are compared. The main attention is focused on Chinese and Russian grammar differences and their influence on the teaching process. Chinese students are to understand and learn these differences at the very beginning of the training process. This fact is very important as the period of accumulation of lingual images by the Chinese students is long enough. On this occasion the main differences in Chinese and Russian phonetics have been described. The article contains some advices on optimization of the training process such as modernization and elaboration of nationally-oriented text-books according to their native language (mother tongue). The workout of some methodical materials in which cultural and linguistic peculiarities of different ethnic groups of students will be analyzed and recommendations